Flow Cytometry Method Validation Protocols. Issue 1 (12th November 2018) - Selliah, Nithianandan; Eck, Steven; Green, Cherie; Oldaker, Teri; Stewart, Jennifer; Vitaliti, Alessandra; Litwin, Virginia
Abstract: Analytical method validation provides a means to ensure that data are credible and reproducible. This unit will provide a brief introduction to analytical method validation as applied to cellular analysis by flow cytometry. In addition, the unit will provide practical procedures for three different types of validation. The first is a limited validation protocol that is applicable for research settings and non‐regulated laboratories. The second is validation protocol that presents the minimum validation requirements in regulated laboratories. The third is a transfer validation protocol to be used when methods are transferred between laboratories. The recommendations presented in this unit are consistent with the white papers published by the American Association of Pharmaceutical Scientists and the International Clinical Cytometry Society, as well as with Clinical Laboratory Standards Institute Guideline H62: Validation of Assays Performed by Flow Cytometry (currently in preparation). © 2018 by John Wiley & Sons, Inc.